Pengaruh Motivasi, Disiplin Kerja terhadap Kinerja Pegawai PT Pegadaian (Persero) Cabang Sekip Palembang - Nadya Yolanda Hidayat; A. Jalaludin Sayuti; Neneng Miskiyah (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
Employee performance is the most important factor in a company because it affects company income, if the company does not pay attention to employee performance then the company will not run in accordance with company goals, factors that affect employee performance are motivation from oneself and others, leadership, and work discipline employee. Of the two factor that affect employee performance, the authors are interested in conducting research on the effect of motivation, work discipline on employee performance at PT Pegadaian (Persero) Â Cabang Sekip Palembang, the population in this study used saturated sampling, so all employees at PT Pegadaian (Persero) Cabang Sekip Palembang would be sampled many as 42 people. The analysis technique in this study uses t test, Â f test. These results show that motivation, work discipline have a positive or significant effect on the performance of employees of PT Pegadaian (Persero) Cabang Sekip Palembang, which is 204,800 > 3.23 and the sig value is 0.000 < 0.05. Â